Classification Rule Generation for Cancer Prediction using Locality Sensitive Hashing Similarity Measure - Amiya, Gautam; Anuradha, J; B, Venkatesh (International Journal of Engineering and Technology, 2018)
This paper aims to develop a decision support system for healthcare in predicting stage of cancer (whether benign or malignant) using a novel classifier technique based on Locality Sensitive Hashing (LSH). We propose a new classification rule generations scheme based on Locality Sensitive Hashing. By applying LSH based classification instance selection algorithms, we get a minimal set of class representative patterns, on which we apply discretization and classification rule generation manually. Thus, have high chances of coming up with best prediction. Confusion matrix is used to compare test results. The above technique is applied on two datasets –Iris and Breast Cancer Wisconsin. We get better accuracy, specificity, sensitivity and precision than traditional classifiers. Manual diagnosis takes time and is a trial-error procedure and needs knowledge from medical specialists. We better the accuracy and speed of this manual procedure. classification model concept is used.
Keywords: CBR (Case Based Reasoning); Discretization; Euclidean Distance Metric; Gaussian distribution; LSH (Locality Sensitive Hashing).